2022
DOI: 10.1200/jco.2022.40.16_suppl.7513
|View full text |Cite
|
Sign up to set email alerts
|

Interim results of a phase II multicenter study with the oral histone deacetylase inhibitor abexinostat in patients with relapsed/refractory follicular lymphoma.

Abstract: 7513 Background: Follicular lymphoma (FL) is generally considered incurable with patients (pts) often experiencing multiple relapses requiring varying lines of subsequent treatments. Abexinostat (Abx) is a novel potent oral pan- Histone Deacetylase Inhibitor (HDACi) with a pharmacokinetic profile that allows maintenance of sufficient drug concentrations for anti-tumor activity with twice daily (BID) dosing. In prior phase 1/2 studies, Abx was shown to be well-tolerated with significant clinical activity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Higher response rates have been reported in other HDAC inhibitor studies. A recent trial of abexinostat in 37 patients with FL showed a response rate of 70% [ 19 ]. Differences may be due to patient population or the therapy itself; abexinostat is a pan-HDAC inhibitor, which may have different anti-lymphoma activity compared to the HDAC1-selective activity of mocetinostat.…”
mentioning
confidence: 99%
“…Higher response rates have been reported in other HDAC inhibitor studies. A recent trial of abexinostat in 37 patients with FL showed a response rate of 70% [ 19 ]. Differences may be due to patient population or the therapy itself; abexinostat is a pan-HDAC inhibitor, which may have different anti-lymphoma activity compared to the HDAC1-selective activity of mocetinostat.…”
mentioning
confidence: 99%